PERBEDAAN KUALITAS JENIS ES BATU BERDASARKAN KANDUNGAN ESCHERICHIA COLI DI WARUNG MAKAN KELURAHAN TEMBALANG - Evi Nurmalasari; Sri Yuliawati; Nissa Kusariana; Retno Hestinigsih (Jurnal Kesehatan Masyarakat (Undip), 2019)
Ice cube is cooling material used as mixed drinks for consumption,, but ice used can be contaminated by pathogenic microorganisms such as coliform and escherichia coli that can cause disease. As for the types of ice cubes that are widely circulated in the community is crystal ice cubes and plastic packaging ice cubes. The purpose of this research is to distinguish the quality of this type of crystal ice cubes and plastic packaging ice cubes to the content of pathogenic Escherichia coli. This type of research is analytic research using a cross sectional approach and laboratory tests. The population of the research was the food stalls that sell ice cubes for mixed drinks in Tembalang village. The size sample research is 31 crystal ice cubes and 31 plastic packaging ice cubes with the method of purposive sampling. Data collection uses  observation sheets, questionnaires, and laboratory tests. Each sample is examined through the planting medium Lactose Broth, Mac Conkey and Triple Sugar Iron Agar. Data analysis using univariate analysis and bivariat  analysis using Chi square test. Results univariate showed as many as 20 (32.3%) samples contaminated with pathogenic Escherichia coli.The presence of Escherichia coli more found on Crystal ice cubes (63.2%) than ice cubes of plastic packaging. Bivariat analysis showed no meaningful difference in the quality of crystal ice cubes and  plastic packaging  ice cubes (p = 0,416). Based on the results of the analysis it can be concluded that there is no difference in the quality of crystal ice cubes and plastic packaging ice cubes based on the existence of pathogenic Escherichia coli.